1998
DOI: 10.1136/jcp.51.9.700
|View full text |Cite
|
Sign up to set email alerts
|

Jejuno-ileal bypass, enteric hyperoxaluria, and oxalate nephrosis: a role for polarised light in the renal biopsy

Abstract: Enteric hyperoxaluria, a complication of jejuno-ileal bypass, is associated with renal failure owing to oxalate nephrosis or tubulo-interstitial nephritis. A 54 year old woman developed renal failure 17 months after jejuno-ileal bypass for morbid obesity. Renal biopsy showed widespread acute on chronic damage to the tubulointerstitial compartment with extensive deposition of oxalate crystals. The extent of oxalate deposition was only evident on polarisation of the biopsy. (J Clin Pathol 1998;51:700-702)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…[6,7] Increasing awareness of enteric hyperoxaluria complicating jejunoileal bypass surgery and Roux-en-Y gastric bypass progressing to oxalate nephropa-thy (ON) and renal failure offers reason for pause and concern. [8][9][10][11][12][13][14] An index case of oxalate nephropathy occurring in the transplanted kidney in a recipient that had received jejunoileal gastric bypass (GB) prior to transplantation at our center prompted us to examine outcomes among our post-gastric bypass renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Increasing awareness of enteric hyperoxaluria complicating jejunoileal bypass surgery and Roux-en-Y gastric bypass progressing to oxalate nephropa-thy (ON) and renal failure offers reason for pause and concern. [8][9][10][11][12][13][14] An index case of oxalate nephropathy occurring in the transplanted kidney in a recipient that had received jejunoileal gastric bypass (GB) prior to transplantation at our center prompted us to examine outcomes among our post-gastric bypass renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…By light microscopy, calcium oxalate crystals are gray-white and spiculated. Most importantly, they are birefringent under polarized light, whereas calcium phosphate crystals do not polarize (5,17,18). In this series, all patients had biopsy-proven AON.…”
Section: Discussionmentioning
confidence: 83%
“…Oxalate precursors incriminated in toxic or drug-induced AON include acute poisoning by ethylene glycol (8) and ascorbic acid (21), respectively. Enteric hyperoxaluria has been described in various malabsorptive intestinal diseases, like jejuno-ileal bypass (17,22), short bowel syndrome (23,24), and chronic inflammatory bowel disease (25)(26)(27). Recently, short series have emphasized the risk of AON after modern bariatric surgery with Roux-en-Y gastric bypass (5,9).…”
Section: Discussionmentioning
confidence: 99%
“…In enteric hyperoxaluria, malabsorbed fat reacts with calcium reducing the formation of CaOx-insoluble compounds in the intestinal lumen, hence raising free oxalate absorption [14][15][16][17]. Several authors have reported that increasing dietary fat also leads to increased bile salt synthesis in rats [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal diseases that have been associated with this entity are those characterized by an absence or nonfunction of the small bowel (enteritis, small bowel resection, or bypass surgery) and those causing defective absorption of fat or bile acids (chronic pancreatitis, biliary cirrhosis, blind loop syndrome, and other diseases) [14][15][16][17]. Unabsorbed bile acids and fatty acids may react with calcium in the intestinal lumen, forming "soaps" that limit the amount of free calcium binding with oxalate, with a consequent increase in intestinal oxalate absorption leading to hyperoxaluria [14,[18][19][20][21][22][23].…”
mentioning
confidence: 99%